Sensory Profile of Cake with the Addition of Nutmeg (Myristica fragrans H.) Essential Oil as a Flavouring Agent - Sipahelut, Sophia Grace (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Utilizing nutmeg pulp into essential oil is an effort to maximize the potential of nutmeg flesh which has so far only been a waste. The content of functional compounds in nutmeg pulp oil can enrich the taste of food products and even provide health benefits. The aim of this research is to examine the effect of essential oils from nutmeg flesh as a natural flavoring agent on the sensory profile of cakes. The experimental design used was a Completely Randomized Design (CRD) with treatment concentrations of nutmeg pulp oil, namely 0%, 0.05%, 0.10%, and 0.15%. The sensory profile observed included color, aroma, taste, and texture. Data were analyzed using ANOVA and continued with Duncan's Multiple Range Test (DMRT) if there were significant differences. The results showed that different concentrations of nutmeg pulp oil affected the aroma, taste and porous texture of the cake, but had no real effect on the color and soft texture of the cake. The addition of nutmeg pulp oil as flavouring agent produces a cake with a bright yellow color, a slightly fragrant aroma typical of cake to a typical cake aroma, no nutmeg aroma to nutmeg aroma, the taste is close to sweet to sweet, the texture is soft and the pores are quite tight. The sensory profile of a cake with the addition of nutmeg pulp oil has the same sensory characteristics as a cake without the addition of nutmeg pulp oil, namely a cake with the addition of 0.05% nutmeg pulp oil.